Efektifitas Pelatihan “Sekolah Otak Papua” untuk Meningkatkan Kemampuan Belajar Mandiri Siswa Sekolah Menengah Pertama - Bolly, Hendrikus Masang Ban; Rumboirusi, Ricky Lazarus; Dewi, Made Ratna (Bahasa Indonesia, 2025)
Physical, mental, and hormonal changes in junior high school students have a particular impact on learning performance. Students are vulnerable to biological changes that affect learning motivation, academic stress, and even procrastination tendencies. All learning activities require optimal brain performance at this level. Students need soft skills, including learning skills based on the performance of the human brain. The Papua Brain School (SOP) is a practical training program specifically designed for junior high school students to learn neuroscience-based learning strategies to improve independent learning performance. The “Sekolah Otak Papua” training aims to equip students with knowledge-based learning strategies and the ability to optimize brain performance. The training was conducted at SMP 5 Jayapura, attended by 31 students over two days. The material consisted of eight topics delivered interactively through direct face-to-face classroom sessions, interspersed with simple practices, video sessions, and games. Evaluation of the training results showed an increase in participants' knowledge related to the topics presented, from 40% correct answers in the pre-test to 86.67% correct answers in the post-test. In the evaluation of the effectiveness and performance of the training, 70.97% agreed that the use of audio-visual media (PPT) was good, 87.09% considered the presenters competent and performed well; 61.29% agreed that the training atmosphere and facilities were good; 77.42% agreed that the training duration was sufficient; and 93.55% agreed that they were motivated to change their brain-based learning strategies and overall material content according to the relevance of the need for changes in learning strategies in junior high schools.   Abstrak Perubahan fisik, mental dan hormonal pada siswa jenjang sekolah menengah pertama memiliki dampak khusus pada performa pembelajaran. Siswa rentan terjadap perubahan biologis yang mempengaruhi motivasi belajar, stres akademik bahkan kecenderungan prokastinasi. Seluruh aktivitas pembelajaran memerlukan kinerja otak yang optimal pada jenjang tersebut. Siswa memerlukan bekal soft skill keterampilan belajar berbasis kinerja otak manusia. Sekolah otak Papua (SOP) merupakan program pelatihan praktis yang dirancang khusus untuk siswa SMP mempelajari strategi belajar berbasis neurosains untuk meningkatkan kinerja pembelajaran mandiri. Pelatihan SOP memiliki tujuan untuk membekali siswa tentang bagaimana strategi pembelajaran berbasis pengetahuan dan kemampuan mengoptimalkan kinerja otak. Pelatihan dilakukan di SMP Negeri 5 Jayapura, diikuti oleh 31 siswa selama dua hari. Materi terdiri atas delapan topik yang disampaikan secara interaktif melalui tatap muka langsung dalam ruang kelas, diselingi dengan praktik sederhana, sesi video dan permainan. Evaluasi hasil pelatihan menunjukkan terjadi perubahan peningkatan pengetahuan peserta terkait dengan topik yang disampaikan dari pre-test menjawab 40% benar menjadi 86,67% benar pada post-test. Pada evaluasi efektifitas dan performa pelatihan sebanyak 70,97% setuju bahwa penggunaan media audio visual (PPT) sudah baik, 87,09% menilai bahwa pemateri kompeten dan berperforma baik; 61,29% setuju bahwa suasana dan fasilitas pelatihan baik; 77,42% setuju bahwa durasi waktu pelatihan cukup; dan 93,55% setuju bahwa mereka termotivasi untuk mengubah strategi belajar berbasis otak dan konten materi secara keseluruhan sesuai dengan relevansi kebutuhan perubahan strategi pembelajaran di SMP.